Description of buckwheat cultivars from Belarus and Ukraine in the environments of Leningrad Province - O. I. Romanova (Труды по прикладной ботанике, генетике и селекции)
Background. Buckwheat is an extremely valuable groat crop in demand both in Russia and abroad. The buckwheat collection held by VIR is the largest in the world. Studying and systematizing knowledge about the conserved diversity of the genus Fagopyrum Mill. representatives cannot be efficient without switching to the use of the most detailed descriptors containing plant characters least dependent on differences in growing conditions.Materials and methods. Seventeen buckwheat cultivars from Ukraine and Belarus and two references from Russia were studied in Leningrad Province. The methodological basis of the study included the IPGRI buckwheat descriptors and personal recommendations of N. V. Fesenko. Statistical data processing was performed according to P. F. Rokitsky.Results. The cultivars formed their typical plant habitus and demonstrated good fruit setting − an average score was 3.3–4.9 out of five. The determinant stem growth was observed in 10 cultivars. The stem developed 2.7−6.7 generative nodes and 4–6 vegetative ones, while 1.9–4.7 generative and 0.8−2.3 vegetative nodes were formed on the two upper branches.Conclusion. The study confirmed that medium-ripening buckwheat can be grown in Leningrad Province. The modal value of the number of vegetative nodes for the studied cultivars was 4−5, which is an indicator of intermediate ripening. The results of studying the metamerism of the stem and the two upper branches, expressed by modal values, were recorded in the “agricultural fitness” passport for the tested cultivars as follows: determinant stem; branching zone 4+1+2; fruit-forming zone 3+3+3; average score of fruit formation 4.8. The presented data format most fully characterizes a cultivar in terms of the potential of its earliness and productivity. Depending on the task, indicators for the main stem or for the two upper branches can be used. Recording values in the form of a formula is convenient and does not imply any other meanings.